Minat Berwirausaha Pada Siswa SMKN - Putri, Amemiya Maneko; Setiawati, Tati; Nurhayati, Ai (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2023)
Catering graduates at SMKN 9 Bandung who have become entrepreneurs in the last 3 years have the lowest percentage compared to those who are working or continuing. Even though students have been provided with Creative Projects and Entrepreneurship (PKK) subjects that support entrepreneurship, The purpose of this study was to determine the factors influencing interest in entrepreneurship among students at SMKN 9 Bandung. The method used in this study is descriptive-quantitative data collection using a questionnaire. The population in this study was 101 who had passed the Creative and Entrepreneurship Project (PKK) subject, and we used the total sample so that the number of samples was equal to the total population. The results showed that the internal factors of students’ interest in entrepreneurship were in the high category. The highest internal factor score is on the feeling of pleasure indicator and is in the high-high category. Meanwhile, the lowest internal factor score is on the motivation indicator and is in the high category. The highest score is based on external factors, namely the school environment, and is in the high category. Meanwhile, the lowest external factor score is on the community environment indicator and is in the high category